728 Sleep Apnea Screening in Inpatients Admitted with Acute Exacerbation of Chronic Obstructive Pulmonary Disease: A feasibility study. (3rd May 2021) - Lastra, Alejandra; Esmero, Veronica; Herdegen, James; Durkin, Colleen
Abstract: Introduction: Obstructive sleep apnea (OSA) and Chronic obstructive airway disease (COPD) affect millions of Americans. The combination (overlap syndrome) results in increased morbidity, mortality and associated healthcare costs. Type III sleep testing via portable monitoring (PM) is not recommended for patients with COPD, and there is little guidance in regards to inpatient testing. We aim to determine the feasibility of inpatient PM for diagnosing OSA in patients admitted with acute exacerbation of COPD (AECOPD) and hypercapnic respiratory failure requiring noninvasive positive pressure ventilation (NIPPV). Methods: This is a retrospective review of prospectively collected data. Inpatients 40 year-old and older admitted with AECOPD and PaCO2≥52mmHg on arterial blood gas (ABG) testing requiring NIPPV were included for analysis. One patient died and one withdrew consent. The remaining patients underwent overnight PM (ApneaLink Airtm by ResMed®) once clinically stable, off NIPPV, on oxygen when needed to sustain oxygen saturation at or above 88%. Patients were discharged on volume-assured pressure support ventilation (VAPS) for nightly use at home and followed for 6 months. Results: Five patients were included. Average age was 60 years, majority were African-American males, former smokers (average 31.2 pack-years), with moderate to severe airflow obstruction (FEV1 24–52 %Pred). Except for one (BMI 17 kg/m2), patients had concomitant morbid obesity (average BMI 39.7 kg/m2). Four out of 5 patients had overlap syndrome (AHI 19.4/h -75/h). Follow-up objective download data demonstrated AHI <10 in all patients with available data (3/5 at 6 months). One patient required in-sleep center VAPS titration. Conclusion: This pilot study suggests portable monitoring is feasible in diagnosing OSA in this complex patient population admitted for AECOPD, despite concomitant oxygen use during PM testing. Despite the small number of patients, 4/5 were diagnosed with moderate to severe OSA and objective data on VAPS demonstrated effective treatment. Further studies using PM for screening of OSA in inpatients with COPD and obesity and impact on patient-centric outcomes are needed. Support (if any):